Leon F. Lyday and George W. Woodyard, A bibliography of Latin American theatre criticism 1940-1974. University of Texas, Austin, 1976; xviii + 243 pp. - Venier, Martha Elena (El Colegio de México, 1978)
Se reseñó el libro: A bibliography of Latin American theatre criticism 1940-1974.